My scrapbook journal : a creative guide to scrapbooking & collage - Fischer, Alina (OH! Life, 2024)
A beautiful and practical craft book by scrapbook journaling TikToker Flinasday, aka Alina Fischer, including Flinasday's most popular pages and her top tips on how to achieve effects. Indulge your artistic side, explore your imagination and record your thoughts or life in your own personalized scrapbook journal, collaged with ephemera and embellished with stickers, cut-outs and motivational quotes.